Flood Risks in Sinking Delta Cities: Time for a Reevaluation?. Issue 8 (21st August 2020) - Yin, Jie; Jonkman, Sebastiaan; Lin, Ning; Yu, Dapeng; Aerts, Jeroen; Wilby, Robert; Pan, Ming; Wood, Eric; Bricker, Jeremy; Ke, Qian; Zeng, Zhenzhong; Zhao, Qing; et al.
Abstract: Sea level rise (SLR) and subsidence are expected to increase the risk of flooding and reliance on flood defenses for cities built on deltas. Here, we combine reliability analysis with hydrodynamic modeling to quantify the effect of projected relative SLR on dike failures and flood hazards for Shanghai, one of the most exposed delta cities. We find that flood inundation is likely to occur in low‐lying and poorly protected periurban/rural areas of the city even under the present‐day sea level. However, without adaptation measures, the risk increases by a factor of 3–160 across the densely populated floodplain under projected SLR to 2100. Impacts of frequent flood events are predicted to be more affected by SLR than those with longer return periods. Our results imply that including reliability‐based dike failures in flood simulations enables more credible flood risk assessment for global delta cities where conventional methods have assumed either overtopping only or complete failure. Plain Language Summary: Sea level rise is expected to exacerbate dike failures and flood hazards in sinking delta cites. With the case in Shanghai, we demonstrate that flood risks in many delta cities globally could be better understood, as most flood risk modeling exercises assumed either complete dike failure or overtopping only but neglected the interaction between dike reliability, land subsidence, and flood risks, thereby likely either overestimating or underestimating future risks. The transferrable framework presented herein contributes to more robust risk assessments for other global delta cities facing significant relative sea level rise and flooding challenges. Key Points: We combine reliability analysis with hydrodynamic modeling to quantify relative SLR effect on dike failures and flood hazards for Shanghai Relative SLR may result in unprecedented and nonlinear impacts on dike failure‐induced flooding in Shanghai and other sinking delta cites Including reliability‐based dike failures in flood simulations contributes to more robust flood risk assessment for sinking delta cities